Pemanfaatan Internet of Things Pada Pintu Dan Kipas Angin Otomatis Di Rumah Kos - wiwi, muhammad hibrian; saharis, risky (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2024)
The growth of society and students is getting higher from year to year, this is because it is inseparable from the development of the world of education, where people tend to control their home electrical appliances using switches manually that must be operated with human power. The use of technology that can be utilized from this internet network is to be able to access electronic equipment such as lights, fans, air conditioners and other electronic equipment in a room that can be turned on and off via smartphone.  A prototype or model of a door that can be controlled remotely, meaning that the door can be opened and closed via a smartphone connected to a mobile phone. So the electronic devices that have been carried out research can be controlled via smartphones connected to the internet successfully carried out.Keywords: IoT, Wemos D1 Mini, Selonoid,